Climate action contributor and carbon space appropriator: national image construction of China in dual-carbon commitment from Indian media’s perspective - Yuxin Wu; Xiufeng Zhao (Humanities & Social Sciences Communications)
Abstract China’s commitment in 2020 to its dual-carbon goal, demonstrating its intention to participate in tackling climate crisis, drew the attention of international media, particularly the media of India, which tends to deem China a rival neighbour. Indian media continually reported this announcement and subsequent policies and actions in China, reflecting Indian cognition and attitude toward China’s commitment to climate change and the Sino-Indian relationship. Given that, the present study adopts the Discourse-Historical Approach (DHA), using corpus tools Sketch Engine (SkE) and KH Coder to identify and visualise the topics of the 127 reports collected from three mainstream English newspapers in India, namely The Times of India, The Indian Express, and Hindustan Times, analysing the major discursive strategies including nomination, predication, and perspectivization strategy, and explores the national images of China constructed by the reports and uncovers the hidden ideology. The study finds that Indian media are mainly concerned with China’s target, plan, and conditions of the dual-carbon commitment, resorting to specially designed references, negative evaluations, and perspectivization strategies like indirect speech to target China’s energy practice, casting doubt on China’s capability to realise its goal. As regards China’s national image, Indian media construct China as a significant contributor to global climate action while evaluating its international role as a carbon space ‘appropriator’, with ‘too ambitious’ carbon goals and ‘disappointing’ carbon practices. In general, such construction reflects, to some degree, India’s tension against China’s rapid rise in climate governance. In addition, the competition for discursive rights in international carbon politics can also provide an account of the negative construction. The present study visualises the topics and the semantic features, promoting further integration of critical discourse analysis with corpus linguistics. Meanwhile, this analysis contributes to China-related international and regional media studies.